Gender-specific association between the regular use of statins and the risk of irritable bowel syndrome: A population-based prospective cohort study - Zhang, Xiaoying; Liu, Yuyao; Ou, Yanghui; Yang, Man; Yuan, Jinqiu; He, Qiangsheng; Li, Yanfei; Mi, Ningning; Xie, Peng; Li, Wenjing; Wu, Siqin; Qin, Xiwen; et al. (Frontiers in Pharmacology, 2023)
Introduction: In addition to lipid-lowering effects, statins might modulate the gut microbiome and alleviate systematic inflammation, which in turn, may have a protective effect against irritable bowel syndrome (IBS). The aim of our study was to evaluate the gender-specific association between statin exposure and the risk of IBS. Method: We undertook a prospective analysis based on the United Kingdom Biobank, a large ongoing cohort including 477,293 participants aged 37–73 years. We included participants based on information on their personal statin use and also those free of IBS and cancer at the baseline. We evaluated the gender-specific hazard ratio (HR) and 95% confidence interval (CI) with Cox proportional hazards regression, adjusting for demographic factors, lifestyle factors, comorbidities, and statin indications. Result: A total of 438,805 participants (206,499 males and 232,306 females) were included in the analysis. Among male participants, the regular use of statins was associated with a decreased risk of IBS (HR: 0.77; 95% CI: 0.61–0.97). This association persists across multiple sensitivity and subgroup analyses and did not show clear evidence of variance among the major types of statins. We did not find sufficient evidence of the association between the statin use and IBS risk in females (HR: 0.98; 95% CI: 0.82–1.16). Conclusion: Our study found that the regular use of statins was associated with a decreased risk of IBS in male participants. Further studies are required to confirm the beneficial effect of statins.